Looking back, looking forward: Central and Eastern Europe 30 years after the fall of the Berlin Wall - Richard Grieveson; Vladimir Gligorov; Peter Havlik; Gábor Hunya; Olga Pindyuk; Leon Podkaminer; Sándor Richter; Hermine Weinberger-Vidovic (The Vienna Institute for International Economic Studies (wiiw), 2019)
To mark the 30th anniversary of the fall of the Berlin Wall, this paper aims to assess developments in Central, East and Southeast Europe (CESEE) over the past three decades, and to look forward to what the next 30 years might bring. First, we measure the convergence of per capita income, wages and life expectancy in CESEE with Western Europe since 1989, and examine demographic trends. We find that, after a difficult start, many countries have become significantly wealthier and their populations much healthier. However, for others, the outcomes of the first 30 years are less positive, and a large number of countries in CESEE have already experienced significant population decline. Second, our experts look back at the situation in 1989, and to what extent their expectations have played out, reflecting on both successes and disappointments. Third, we analyse current trends in the region, and attempt to project what will come next. Here, we focus on automation, digitalisation, institutions, demographics and geopolitics. We find evidence of institutional regression, demographic challenges, and a changing geopolitical backdrop which will have important implications for much of the region. However, we also see reasons for optimism, including the opportunities provided by digitalisation and automation, and an active civil society that could in time force positive change.
Keywords: E00; E02; F02; J11; P20; P30; O52; 330; CESEE; Europe; Central and Eastern Europe; transition; convergence; demographics; CESEE; Europe; Central and Eastern Europe; transition; convergence; demographics